If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -1(-5) = -27 Multiply -1 * -5 -7 + 5 = -27 Combine like terms: -7 + 5 = -2 -2 = -27 Solving -2 = -27 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| x^2+5/2x+c=0 | | 7y^2-17y+6=0 | | 0.5^(x/13.1) | | 5(9+3x)= | | x^2-2.4x+c=0 | | 4(8-2x)+2x= | | 8=2y+3 | | x/4-2x/5=6 | | x-0=-5 | | 3(y-5)=6y+9 | | 3y-5=6y+9 | | (8x+10)2= | | 0.5(x+20)+0.9x=59 | | 3y-5=6 | | 4.74=71.25x | | (2x+1)(4x+2)(3)= | | 5t+10(t+14)+25(t+6)=850 | | exp(x)=y | | 0.07t+0.09(t+500)=109 | | 2y-(y+3)=-8 | | 2(a-4)+5(4a)=-96 | | ((2x+1)/(x-3))-((x-4)/(x+5))=-((10x+13)/(x+5)) | | 2/5*x=8 | | y=1/4(-2)-2 | | .3a+0.8(35-a)=18 | | 0.33333x-0.75=0.83333x+0.5 | | -3x-(5x+1)=7 | | -5(5y-5)+3(3y+7)=34y-46 | | -(5b-5)+3=2-(5b+5) | | -10=x/-8-3 | | -5(5y-5)+3(3y+7)= | | 4(x+3)-(4x-1)=4(4x-3)-7 |